Co-integration theory-based cluster time-varying load optimization control model of regional integrated energy system - Zhang, Anan; Zheng, Yadi; Huang, Huang; Ding, Ning; Zhang, Chengqian (Energy (Oxford), 2022)
The industrial park is an area zoned and planned for the purpose of industrial development. Although it contributes to economic growth and social development, it is also the main area of carbon emission. However, the industrial park always faces the problems of imbalances between supply and demand, which have a huge impact on the goal of energy saving and consumption reduction. Therefore, by studying the source-load interaction problem of the regional integrated energy system, this paper conducts energy supply and demand side management, which achieve lean control of regional loads. First of all, based on the time-varying characteristics of the distributed load in the region, cluster the loads and analyze the supply and demand trends for clusters. After that, considering the production process parameters, decentralized autonomous control is implemented for the cluster time-varying load. Lastly, the validity and accuracy of the model are verified by applying the model to the oilfield production area and the offshore oilfield platform system. The results show that the source-load co-integration model achieves the supply and demand matching in regional integrated energy system. Solve the problem that non-stationary time series may create spurious regression. In addition, it can be seen from the simulation results of the examples, the co-integration-based cluster control strategy improves the energy utilization by nearly 40%, which helps to achieve the goal of regionally efficient and stable production. •Establish a supply-demand co-integration model from a time series perspective.•A proof method considering non-stationary time series is proposed.•Establish a multi-type time-varying load scheduling model in industrial parks.•Implement the distributed control strategy of cluster time-varying load.